KNOWLEDGE, ATTITUDES AND PREFERENCES AMONG SPANISH COMMUNITY PHARMACISTS REGARDING INHALED THERAPY (THE OPTIM PHARMACY STUDY) - Giner, Jordi; Roura, Pere; Torres, Berta; Burgos, Felip; Castillo, Diego; Tarragona, Eduard; Plaza, Vicente (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To assess knowledge, attitudes, and preferences regarding inhaled therapy among Spanish community pharmacists. Methods: An 11-item questionnaire was developed and distributed to community pharmacists throughout the country. Data collected included demographics, the source of knowledge of inhaler use, known and preferred devices, steps for correct use of metered-dose (pMDI) and dry-powder (DPI) inhalers, important variables when prescribing an inhaler device, patient education, and checking inhaler technique. Results: Of a total of 3000 questionnaires delivered, 1722 (57.4%) were returned. The most common source of knowledge was the package insert (46.9%) followed by personal experience (33.3%). DiskusTM and TurbuhalerTM were the best-known devices (96.4% and 93.4%), and DPIs the preferred inhalers. Although more than half of the surveyed pharmacists were aware of the most important step for correct inhalation with pMDI and DPI, only 18% identified the correct answer ‘Patient's preference' as the most important variable when prescribing an inhaler device. Most of the respondents had inadequate knowledge of inhaled therapies. Statistically, significant differences were found according to geographical areas. Moreover, the mean score on inhaled therapy with one knowledge source was higher than for those with none (P<0.05). Additionally, patient education was poor. Conclusion: In spite of the increasing involvement of Spanish community pharmacists in patients' care, their knowledge of inhaler use and attitudes towards inhaled therapy needs to improve, so that they can provide better patient education.